Numerical and experimental validations of the theoretical basis for a nozzle based pulse technique for determining building airtightness. (15th January 2021) - Cooper, Edward; Zheng, Xiaofeng; Wood, Christopher J.
Abstract: Motivated by intentions of avoiding large net fluid flow and enabling a more practical airtightness test for large buildings, a low-pressure Pulse pressurisation technique was developed for measuring building airtightness at pressures that are considered more representative of that experienced by buildings under natural conditions. Due to the short and dynamic operation, this technique is able to minimize wind and buoyancy effects during the measurement of building pressure. The investigation, based on the "quasi-steady" temporal inertia model, explores a technique that generates a pressure pulse inside a building by releasing a known amount of air pulse over 1.5 s using a compressed air tank. The volumetric flow rate of the air pulse released from the tank is obtained by measuring the transient pressure in the air tank during a test run. The air leakage through the building envelope is then obtained by accounting for the compressibility of indoor air. Simultaneously, the pressure variation within the envelope of test building is monitored. Therefore, the leakage-pressure relationship of the building envelope can be obtained. The validity of the theoretical model and the assumptions on which the model is based are validated using experimental and numerical investigations. Highlights: A low-pressure Pulse technique for measuring building airtightness is introduced. Theoretical model and its assumptions are validated numerically and experimentally. It proves the pressure distribution in tank and building is uniform. A close agreement with the steady test is obtained under a sheltered condition. Error analysis shows that the experimental validation is reliable.